2015
DOI: 10.1016/j.ultrasmedbio.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Changes Correlated with Temperature Increases Induced by High-Intensity Focused Ultrasound Ablation

Abstract: To gain better understanding of the detailed mechanisms of high-intensity focused ultrasound (HIFU) ablation for cardiac arrhythmias, we investigated how the cellular electrophysiological (EP) changes were correlated with temperature increases and thermal dose (cumulative equivalent minutes [CEM43]) during HIFU application using Langendorff-perfused rabbit hearts. Employing voltage-sensitive dye di-4-ANEPPS, we measured the EP and temperature during HIFU using simultaneous optical mapping and infrared imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…17,25,36 A recent study reported that an irreversible electrophysiological change in cardiac tissue could be induced when focal temperature increased above 52.3°C ± 1.4°C using high-intensity focused ultrasound. 37 Brain tissue is well known to be more thermally sensitive than other parts of the body, and its threshold for permanent lesioning can be low. 11 In this study, a maximum temperature of less than 50°C was unable to form tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…17,25,36 A recent study reported that an irreversible electrophysiological change in cardiac tissue could be induced when focal temperature increased above 52.3°C ± 1.4°C using high-intensity focused ultrasound. 37 Brain tissue is well known to be more thermally sensitive than other parts of the body, and its threshold for permanent lesioning can be low. 11 In this study, a maximum temperature of less than 50°C was unable to form tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The Arrhenius equation, Pennes' bioheat equation, and the cumulative equivalent minute at 43 are relevant principles related to tissue ablation and hyperthermia treatment. 33,34 The Arrhenius equation principle can be model collagen heating, indicating that the rates of collagen reactions depend on both time and temperature. If high temperatures are reached, low exposure times are required.…”
Section: R Ad I Ofrequen C Y Ther Apy In the Tre Atment Of S K In L A...mentioning
confidence: 99%